ISSUE OF NEUTRALIZATION OF VULNERABILITIES INFORMATION AND COMMUNICATION SYSTEMS OF CIVIL AVIATION: LEGAL ASPECT - Krivolap, Evgeniy; Іurynets, Julia; Belkin, Leonid (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The aim of the article is to research modern approaches to legal regulation in the field of detection, neutralization and management of vulnerabilities in information and communication systems, including civil aviation. Research methods: documentary analysis, summarization of legal information, information from the field of cyber protection of information and communication systems, as well as practices of cyber protection of information from various cyber attacks. Results: it was established that in the most concentrated form, system vulnerability should be understood as the inability of the system to resist the implementation of a certain threat or set of threats, which is especially dangerous in air transport. In this regard, the issue of combating cyber threats becomes the subject of special attention in the aviation sphere, including the International Civil Aviation Organization (ICAO), as well as other international organizations in the field of air transport (International Air Transport Association (IATA), International Coordinating Council of Aerospace Industries Associations (ICCAIA), etc.). In Ukraine, the State Civil Aviation Safety Program is approved by law. At the same time, the strengthening of cyber security in aviation transport is carried out in the context of the introduction of general methods and principles of cyber security. An important step in the introduction of the vulnerability neutralization system in Ukraine should be considered the legislative regulation of Bug bounty procedures - testing of electronic services with the involvement of external specialists, which makes it possible to identify vulnerabilities and flaws in software products. Regulation is carried out by the Procedure for searching and identifying potential vulnerabilities of information (automated), electronic communication, information and communication systems, electronic communication networks, approved by the Cabinet of Ministers of Ukraine Resolution No. 497 of 05/16/2023. Discussion: improvement of legal regulation in the field of detection, neutralization and management of vulnerabilities of information and communication systems, including civil aviation, will contribute to increasing the safety of civil aviation.